Some New Trinuclear Vanillin Schiff Base Complexes of Cobalt, Nickel and Copper - Issam Sallomi; Wijdan Al-Zeadan (College of Education for Pure Sciences, 1970)
ABSTRACT In this study homo and hetero trinuclear complexes of cobalt (II), nickel (II) and copper (II) were prepared by the reaction of their salts (chloride and nitrate) with a Schiff base ligand derived from vanillin and malonylhydrazide. Complexes of the general formulae: [M3(VMH4)2X6)], [M2M'(VMH4)2X6], [MM'M"(VMH4)2X6] and K2[M3(VM)2], K2[M2M'(VM)2], K2[MM'M''(VM)2] (where M, M', M" are the dipositive ions of cobalt, nickel and copper, respectively, VMH4, VM are the neutral and tetra basic forms of the ligand and X= Cl, NO3) were isolated from both neutral and basic media, respectively. The ligand and its complexes were characterized by using analytical, physical and spectral methods. The studies revealed the hexadentate nature of the ligand which gave hexacoordinated and tetracoordinated metal complexes with the most probable octahedral and tetrahedral or square planar structures in neutral and basic media, respectively. The stability period and the stability constants of some of these complexes in neutral solution have been studied spectrophotometrically. The compositions of the complexes were determined by the use of Job method. The results indicate the formation of only 1:1 metal: ligand complexes with similar stability constants.